Audio-Guided Mindfulness Meditation During Transcranial Magnetic Stimulation Sessions for the Treatment of Major Depressive Disorder: A Pilot Feasibility Study - Cavallero, Fiamma; Gold, Michael C.; Tirrell, Eric; Kokdere, Fatih; Donachie, Nancy; Steinfink, Dan; Kriske, Joseph; Carpenter, Linda L. (Frontiers in Psychology, 2021)
Background: Mindfulness-Based Cognitive Therapy (MBCT) has been shown to enhance long-term treatment outcomes for Major Depressive Disorder (MDD), and engagement of specific brain activities during brain stimulation may produce synergistic effects. Audio-guided meditation exercises are a component of MBCT that might be combined with standard Transcranial Magnetic Stimulation (TMS) therapy sessions. We developed and pilot tested a modified MBCT protocol for patients undergoing a standard course of TMS for MDD. Methods: Four MBCT audio-tracks with differing durations and types of mental focus were selected. Patients listened to the audiotapes through headphones during daily TMS sessions for 5 consecutive weeks. The primary goal was to evaluate feasibility and acceptability of the meditation intervention with TMS. Changes in self-rated measures of symptom severity, stress, life satisfaction, and mindfulness were also assessed. Results: 17 depressed subjects completed the study and 12 terminated early. Reasons for discontinuation included inability to meditate in the treatment setting and induction of negative mood states. TMS percussive sensations and clicking sounds hindered patients’ ability to fully concentrate on or clearly hear the audiotape narrator’s voice. Some became overwhelmed or felt increased pressure, anxiety, or aggravation trying to do meditation exercises while receiving TMS. Conclusion: There is a growing interest in combining TMS with other concurrent psychotherapeutic interventions to optimize treatment outcomes. Our results highlight numerous feasibility issues with MBCT via guided audiotapes during TMS treatment. Future work should draw on these shortcomings to evaluate the appropriateness of MBCT for depressed patients undergoing neuromodulation.